Manganan: Jejak Akulturasi Islam dan Budaya Lokal di Margorejo Kerek - Sani Latifatul Khilmina; Dita Karina Putri; Nurul Hakim (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to examine the traces of acculturation between Islam and local culture in Margorejo Village, Kerek District, Tuban Regency. The research is based on the understanding that the spread of Islam in Indonesia occurred peacefully, persuasively, and adaptively, allowing Islamic teachings to interact harmoniously with local traditions without eliminating existing cultural identities. This process produced forms of religious culture that combine Islamic values with local customs and continue to be preserved by the community. The study employed a qualitative descriptive approach. Data were collected through observation, interviews with religious leaders, community leaders, and local residents, as well as documentation of religious and social traditions. Data analysis was conducted through data reduction, presentation, and conclusion drawing. The findings show that acculturation is reflected in the tradition of pilgrimage to the tomb of Sheikh Ahmad Subaqir or Mbah Mboja, who is regarded as an important figure in spreading Islam in the region. The pilgrimage serves not only as a spiritual activity but also as a means of strengthening social solidarity. Another form of acculturation appears in the “sedekah bumi” or “manganan” tradition, which expresses gratitude for agricultural harvests and community welfare. The study concludes that Islam and local culture in Margorejo coexist harmoniously and contribute to strengthening religiosity, social solidarity, and cultural preservation.